2022
DOI: 10.1186/s12872-022-02489-w
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia and its associated factors among adult diabetes outpatients in West Shewa zone public hospitals, Ethiopia

Abstract: Purpose Dyslipidemia is a major risk factor for cardiovascular disease (CVD) in diabetic patients and early detection and treatment can reduce its morbidity and mortality. There is little information on the lipid profile of diabetic patients at West Shewa Public Hospitals, Ethiopia. Therefore, this study aimed to investigate the prevalence and related factors of dyslipidemia among adult diabetes on their follow up at West Shewa Public Hospitals, Ethiopia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
1
6
2
Order By: Relevance
“…Poor glycaemic control is strongly associated with the development of diabetic foot over time ( 50 ). Although the prevalence of unbalanced diabetes was only 36.4% in the present study, previous studies by Fawzy et al ( 48 ) and Abdissa and Hirpa ( 41 ), show a much higher frequency among patients with diabetic feet, at 89 and 63.8%, respectively. These same studies showed that high levels of HbA1c can contribute to the development of the diabetic foot.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Poor glycaemic control is strongly associated with the development of diabetic foot over time ( 50 ). Although the prevalence of unbalanced diabetes was only 36.4% in the present study, previous studies by Fawzy et al ( 48 ) and Abdissa and Hirpa ( 41 ), show a much higher frequency among patients with diabetic feet, at 89 and 63.8%, respectively. These same studies showed that high levels of HbA1c can contribute to the development of the diabetic foot.…”
Section: Discussioncontrasting
confidence: 74%
“…Sex, advancing age, long duration of diabetes, increased body-mass index (BMI) and high blood pressure were risk factors associated with the prevalence of dyslipidaemia ( 39 ). In addition, dyslipidaemia has been previously considered to be an independent predictor of the development of cardiovascular diseases ( 40 , 41 ). In the present study, a close association between obesity (translated into high BMI) and diabetic foot was found, which was consistent with findings from specialized studies ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review of 177 studies at African sites, the prevalence of elevated total cholesterol concentrations, low HDL cholesterol concentrations, and elevated triglyceride concentrations were 34.4%, 39.5% and 3.9%, respectively [19]. A recent study at public hospitals in Ethiopia among mostly urban T2D participants reported dyslipidemia prevalence of 81.5%, with elevated TG being the most common lipid abnormality [20]. A study in South Africa among T2D participants showed dyslipidemia rates of 94.0% and 84.0% among males and females, respectively [21].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of 177 studies at African sites, the prevalence of elevated total cholesterol concentrations, low HDL cholesterol concentrations, and elevated triglyceride concentrations were 34.4%, 39.5% and 3.9%, respectively [20]. A recent study at public hospitals in Ethiopia among mostly urban T2D participants reported dyslipidemia prevalence of 81.5%, with elevated TG being the most common lipid abnormality [21]. A study in South Africa among T2D participants showed dyslipidemia rates of 94.0% and 84.0% among males and females, respectively [22].…”
Section: Introductionmentioning
confidence: 99%